Engineering Multifunctional Hydrogel With Osteogenic Capacity for Critical-Size Segmental Bone Defect Repair - Zheng, Shaowei; Zhong, Haobo; Cheng, Hao; Li, Xu; Zeng, Guowei; Chen, Tianyu; Zou, Yucong; Liu, Weile; Sun, Chunhan (Frontiers in Bioengineering and Biotechnology, 2022)
Treating critical-size segmental bone defects is an arduous challenge in clinical work. Preparation of bone graft substitutes with notable osteoinductive properties is a feasible strategy for critical-size bone defects. Herein, a biocompatible hydrogel was designed by dynamic supramolecular assembly of polyvinyl alcohol (PVA), sodium tetraborate (Na2B4O7), and tetraethyl orthosilicate (TEOS). The characteristics of the supramolecular hydrogel were evaluated by rheological analysis, swelling ratio, degradation experiments, and scanning electron microscopy (SEM). In in vitro experiments, this TEOS-hydrogel had self-healing property, low swelling rate, degradability, good biocompatibility, and induced osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) by upregulating the expression of Runx-2, Col-1, OCN, and osteopontin (OPN). In segmental bone defect rabbit models, the TEOS-containing hydrogel accelerated bone regeneration, thus restoring the continuity of bone and recanalization of the medullary cavity. The abovementioned results demonstrated that this TEOS-hydrogel has the potential to realize bone healing in critical-size segmental bone defects.